Immunostimulatory cellular responses of cured Leishmania-infected patients and hamsters against the integral membrane proteins and non-membranous soluble proteins of a recent clinical isolate of Leishmania donovani - Garg, R (Blackwell Science Inc, 2005)
Development of an effective immunoprophylactic agent for visceral leishmaniasis (VL) has become imperative due to the increasing number of cases of drug resistance and relapse. Live and killed whole parasites as well as fractionated and recombinant preparations have been evaluated for vaccine potential. However, a successful vaccine against the disease has been elusive. Because protective immunity in human and experimental leishmaniasis is predominantly of the Th1 type, immunogens with Th1 stimulatory potential would make good vaccine candidates. In the present study, the integral membrane proteins (IMPs) and non-membranous soluble proteins (NSPs), purified from promastigotes of a recent field isolate, Leishmania donovani stain 2001, were evaluated for their ability to induce cellular responses in cured patients (n = 9), endemic controls (n = 5) of visceral leishmaniasis (VL) and treated hamsters (n = 10). IMPs and NSPs induced significant proliferative responses (SI 6·3 ± 4·1 and 5·6 ± 2·3, respectively; P < 0·01) and IFN-γ production (356·3 ± 213·4 and 294·29 ± 107·6 pg/ml, respectively) in lymphocytes isolated from cured VL patients. Significant lymphoproliferative responses against IMPs and NSPs were also noticed in cured Leishmania animals (SI 7·2 ± 4·7 & 6·4 ± 4·1, respectively; P < 0·01). In addition, significant NO production in response both IMPs and NSPs was also noticed in macrophages of hamsters and different cell lines (J774A-1 and THP1). These results suggest that protective, immunostimulatory molecules are present in the IMP and NSP fractions, which may be exploited for development of a subunit vaccine for VL.